The Effect Of Information Asymmetry, Firm Size, Financial Distress And Capital Structure On Firm Value - Liberti, Pratiwi; Sisi Wardani (Journal of Accounting and Auditing, 2026)
Purpose – This is study aims to test and analyze the relationship between the influence of Information Asymmetry, Firm Size, Financial Distress and Capital Structure on Firm Value  Design/methodology/approach – This study uses a quantitative research approach with secondary data. The sample consists of 57 companies in the primary consumer goods sector (consumer non-cyclical) listed on the Indonesia Stock Exchange between 2022 and 2024. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software.  Findings – The results of this study indicate that information asymmetry affects firm value, firm size variables affect firm value, financial distressand variables affect firm value and capital structure variables do not affect firm value.  Research limitations/implications – This is study was conducted only on the primary consumer goods sector (consumer non-cyclical) during the period 2022-2024. The findings provide instights based on secondary data obtained from company annual report and are expected to be useful for company management, investors, capitas market regulator. And future researchers in understanding the factors that affect firm value.   JEL : G30,G32,G82